Effect of 12 Weeks Aerobic Training with Ginger Consumption on IL-18 and CRP in Obese Men - Mohammad Sorani; khosro jalali; Ali Jalali Dehkordi (Islamic Azad University, 2016)
Introduction: The use of antioxidant and anti-inflammatory supplements is important in improving the function of obese people. The aim of this study was to investigate the effect of 12 weeks aerobic training with ginger consumption on the levels of IL-18 and CRP in obese men. Methods: 40 men (mean ± SD: age 23.9 ± 5.90 years old, weight 87.61 ± 4.69 kg and BMI 32.69 ± 3.25 kg / m2) were randomly selected and divided into four groups of 10, including 1- aerobic training, 2- training with ginger consumption, 3-ginger consumption, 4-control. The first and second groups, had 12 weeks, 3 sessions per week and 40 minutes each session aerobic training selections with an intensity of 65%MHR; during this period, the second and third groups received one gram of ginger capsule daily and the control group received no intervention. Blood samples were taken before and after the study period. Paired sample t-test and one-way ANOVA were used for data analysis (p≤0.05). Results: There was a significant difference in IL-18 and CRP before and after exercise in all three experimental groups (p≤0.05).. Also, the results of the bonferroni post hoc test showed a significant difference in the level of IL-18 and CRP in the Reaserch groups. The highest decrease in these variables was observed in the aerobic training group and training with ginger consumption group (p≤0.05). Conclusion: Ginger supplementation with aerobic training seems to be a suitable method for reducing IL-18 and CRP and preventing metabolic, cardiovascular and inflammatory diseases in obese men.